Determinasi Kinerja Organisasi Peran Disiplin Sebagai Variabel Intervening dalam Hubungan Kepemimpinan, Sarana Prasarana, dan Motivasi terhadap Kinerja Pegawai: Studi pada Kantor Pelayanan Pajak Pratama Ngawi - Muhamad Fajrin Novian Faraitodi; Amir Fikri; Meirani Harsasi (Intitut Agama Islam Nasional Laa Roiba Bogor, 2026)
The performance of Civil Servants as reflected in their performance outcomes, is considered effective when they are able to achieve the assigned administrative targets while adapting to the increasingly dynamic social environment and the evolving needs of the community. Organizational performance is directly influenced by the performance of its individual employees. The better the individual performance, the better the organizational performance, and vice versa. This study employed a descriptive analytical method with a quantitative approach. The population and sample consisted of 76 employees of the Ngawi Primary Tax Office (KPP Pratama Ngawi), including executive staff, Account Representatives, and Tax Auditor Functional Officers. A saturated sampling (census) technique was applied, in which all members of the population were included as the research sample. Data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The results of the study indicate that: (1) leadership style has no significant effect on employee performance; (2) facilities and infrastructure have no significant effect on employee performance; (3) motivation has a positive and significant effect on employee performance; (4) leadership style has no significant effect on employee work discipline; (5) facilities and infrastructure have no significant effect on employee work discipline; (6) motivation has a positive and significant effect on employee work discipline; (7) work discipline has no significant effect on employee performance; (8) work discipline does not mediate the relationship between leadership style and employee performance; (9) work discipline does not mediate the relationship between facilities and infrastructure and employee performance; and (10) work discipline does not mediate the relationship between motivation and employee performance.